Not man enough! Queer Asian masculinities at the field site. - Tang, Shawna; Tang, Denise Tse-Shang (Journal of Gender Studies, 2021)
In this article, we grapple with the ways in which our embodied masculinity affects how we learn about and tell the stories of our older lesbian respondents. Our encounters at the field site have prompted us to think through our methodological practices and epistemological positions, a prompting conditioned by the feminist and queer methodological traditions we are schooled in. Following queer feminist methodological emphasis on attending to the shifting subjectivities of researchers and participants and the concomitant affective registers of the field site, we explore what we call the 'masculine dynamic' between researchers and respondents that hover playfully at the contours of our research encounter. Using ethnographic vignettes and reflection notes, we ask after the interplay of masculine embodiments and performativity at the field site, and what this dynamic might mean for producing a 'knowable' yet largely 'invisible' group of older masculine women in Asia.